Patterns of microglial cell activation in Alzheimer Disease and frontotemporal lobar degeneration - Taipa, Ricardo (2017)
Aims: Microglia-driven neuroinflammation can play an important role in the pathophysiology of neurodegenerative disorders. In this study, we sought to characterize the distribution of microglial cell activation in 2 neurodegenerative dementias with distinct protein signatures, Alzheimer disease (AD) and frontotemporal lobar degeneration (FTLD) of the TDP subtype, and to determine if there was an anatomical correlation with the phenotypes most commonly associated with these conditions. Methods: The distribution and extent of microglial cell activation was assessed semiquantitatively in the hippocampal formation, cortical gray matter, and subcortical white matter of CD68-immunostained sections of the frontal, temporal, parietal, and occipital cortices from 15 pathologically confirmed cases of AD, 13 cases of FTLD, and 18 controls. Results: Significantly higher levels of microglial cell activation occurred in the subiculum in AD and FTLD than in controls. Additionally, AD had higher microglial activation in the CA1 and FTLD in the hippocampal white matter than the controls. Microglial activation was greater in the dentate gyrus molecular layer in AD than in FTLD. In the cortical regions, the 2 pathological groups differed only in frontal white matter, with the FTLD group showing higher microglial scores. FTLD showed higher microglial activation in the white matter compared to the respective gray matter in the entorhinal, temporal, and frontal regions. Conclusions: Our work expands the knowledge of the distribution and magnitude of microglial activation in these disorders. Additionally, we found some microglial circuit-specific patterns that could help to explain some of the clinical overlap between AD and FTLD-TDP, namely in memory deficits.